2004
DOI: 10.1089/cbr.2004.19.738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiation Dose Estimation for Myeloablative Radioimmunotherapy for Relapsed or Recurrent Mantle Cell Lymphoma Using131I Tositumomab to That of Other Types of Non-Hodgkin's Lymphoma

Abstract: Myeloablative RIT using (131)I tositumomab results in normal organ radiation-absorbed doses similar to those in patients with other non-Hodgkin's lymphoma, and is suitable for treating patients with relapsed or refractory MCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Novel therapeutic agents are needed in clinical trials. [4][5][6][7][8] Atiprimod (N-N-diethyl-8,8-dipropyl-2-azaspiro [4,5] decane-2-propanamine), a novel cationic amphiphilic compound, has been studied for its anticancer properties in malignancies. [9][10][11] Recent reports have suggested that atiprimod exhibits antiproliferative and antiangiogenic activities, induces apoptosis via activation of caspases-3 and -8, and inhibits phosphorylation of Akt and STAT3 in multiple myeloma (MM).…”
Section: Introductionmentioning
confidence: 99%
“…Novel therapeutic agents are needed in clinical trials. [4][5][6][7][8] Atiprimod (N-N-diethyl-8,8-dipropyl-2-azaspiro [4,5] decane-2-propanamine), a novel cationic amphiphilic compound, has been studied for its anticancer properties in malignancies. [9][10][11] Recent reports have suggested that atiprimod exhibits antiproliferative and antiangiogenic activities, induces apoptosis via activation of caspases-3 and -8, and inhibits phosphorylation of Akt and STAT3 in multiple myeloma (MM).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Yet even from its earliest days, the clinical prospects of RIT have been hampered by a critical complication: high radiation dose rates to healthy tissues. 5,6 Generally speaking, radioimmunoconjugates for RIT are labeled with long-lived radionuclides -e.g. 131 I (t ½ = 8.0 days) and 90 Y (t ½ = 2.7 days) -with physical half-lives that dovetail well with the long pharmacokinetic half-lives of immunoglobulins.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high-dose radioimmunotherapy (RIT) can deliver potentially curative doses of radiation to tumor sites while limiting the relative radiation exposure to non–target organs [2]. Although previous studies have investigated the total absorbed dose and biological effects of high-dose RIT on the critical organs such as liver and lungs [3, 4], little is known of the effects of high-dose therapy on non-critical organs. For male patients, testicular exposure from high-dose RIT is of concern as it may lead to decreased serum testosterone levels, potentially affecting fertility and quality of life after treatment.…”
Section: Introductionmentioning
confidence: 99%